DISCOURSE ANALYSIS ON TERRORISM-RELATED ARTICLES IN INDONESIAN ENGLISH-LANGUAGE NEWSPAPER EDITORIALS - Ningsih, Lale Fatma Yulia (Humanitatis : Journal of Language and Literature, 2020)
This paper examines the discursive construction of terrorism-related information conveyed on the Indonesian newspapers. The Jakarta Post, one of the most notable Indonesian English-language newspapers, have been covering terrorism related encounters in its editorial especially after the 2002 Bali bombing. This paper finds out the use of common definitions and terms as well as the discrepancies in the produced expression related to terrorism and extremism in the editorials the newspaper has published since 2014. It is found that the newspaper has symphatetically portrayed and supported the victims while it represented the perpetrators from their ideological perspectives and separating their ideologies from religious teaching practices in the country. Additionally, the newspaper identifies terrorism as threat to Indonesian democratic values and classifies terrorism as a serious issue endangering the country’s security and social stability. To the latter end, the newspaper suggested policy recommendation while at the same time criticizing the law enforcement for failures and in the end promoting secular values for the country in order to eradicate terrorism.